Investigation of the sustainability of breastfeeding and infant nutrition in the earthquake region based on mothers' experiences: a qualitative study - Özge Karakaya Suzan; Sümeyra Topal; Sinem Yalnızoğlu Çaka; Nursan Çınar (BMC Public Health)
Abstract Background To explore the breastfeeding status of mothers with children aged 0–2 years after the major earthquake disaster in Kahramanmaraş, to reveal the obstacles to the sustainability of breastfeeding, and to reveal the problems and experiences they have in breastfeeding, preparing formula, and feeding their infants. Methods This study used a qualitative, exploratory research design with a phenomenological approach. Data were collected between September and November 2023 by face-to-face interviews using a Personal Information Form and a semi-structured interview form. A total of 21 participants who breastfed their babies before the earthquake and experienced the earthquake were included in the study, which was conducted using purposive sampling technique. Data were methodologically analysed using inductive coding and thematic analysis procedures. Max Qualitative Data Analysis Analytics Pro2020 software was used to code data. Results The results revealed four primary themes and twenty-two subcategories. The four main themes were; (i) Expectations from Health Personnel, (ii) Suggestions of Mothers, (iii) Difficulties Experienced and (iv) Experiences in Breastfeeding and Infant Feeding. Conclusion The results obtained in this study showed that mothers had problems in terms of information, support, equipment, appropriate area, and food supply related to infant feeding especially in the early post-disaster period. Insights into mothers’ perspectives can help healthcare professionals understand the challenges faced by mothers during disasters and emergencies. In this way, nurses can take the lead in implementing programs designed to support continued breastfeeding and appropriate nutrition for children during disasters.